REDEFINING MOTHERHOOD IN EARLY 20TH-CENTURY BUMIPUTERA WOMEN'S PRESS: Redefinisi Keibuan Dalam Pers Perempuan Bumiputera Awal Abad Ke-20 - Zellica Vanudia Amundari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
In the early 20th century, the emergence of the Bumiputera women’s press became a crucial medium for redefining the roles and identities of women within the colonial society of the Dutch East Indies. This article examines how the concept of motherhood was constructed, negotiated, and redefined through print media managed by and aimed at Bumiputera women. Employing a cultural historical approach combined with discourse analysis, this study explores the construction of motherhood within the contexts of colonialism, early nationalism, and modernity. It reveals that the figure of the "mother" in the press was represented not only as a household caretaker but also as a moral agent, educator of the next generation, and a symbol of women’s collective awakening. This redefinition was influenced by the values of the colonial Ethical Policy, discourses of emancipation, and the role of educated women in shaping a new, public, and national identity. Thus, the concept of motherhood in the early 20th-century Bumiputera women’s press was not static; rather, it served as a contested arena shaped by traditional norms, colonial structures, and the spirit of modernity.